(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the implementation of facility and infrastructure maintenance in the computer laboratory at MIN 1 Palembang. The research is qualitative with a descriptive approach. The study involves 15 informants, consisting of key and supporting informants selected based on criteria and relevance to the subject matter. Data collection methods include interviews, observations, and documentation. Data analysis techniques involve data collection, presentation, verification, and conclusion drawing. The validity of the data is checked through triangulation. The results and discussion indicate that the maintenance of the computer laboratory at MIN 1 Palembang has been carried out properly through several stages: planning, implementation, and evaluation of laboratory maintenance.